2018
DOI: 10.48550/arxiv.1812.08880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First observation of unbound $^{11}$O, the mirror of the halo nucleus $^{11}$Li

T. B. Webb,
S. M. Wang,
K. W. Brown
et al.

Abstract: The structure of the extremely proton-rich nucleus 11 8 O3, the mirror of the two-neutron halo nucleus 11 3 Li8, has been studied experimentally for the first time. Following two-neutron knockout reactions with a 13 O beam, the 11 O decay products were detected after two-proton emission and used to construct an invariant-mass spectrum. A broad peak of width 3.4 MeV was observed. Within the Gamow coupled-channel approach, it was concluded that this peak is a multiplet with contributions from the four-lowest 11 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Other than these isotopes there is only one possible candidate listed in the table: 11 O, posted on the arXiv and submitted for publication in December 2018. 25 If indeed only a few new isotopes are reported during the present year, another update of the discoveries of nuclides at the end of 2019 will not be warranted. The most current status will continue to be posted on the discovery project website.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than these isotopes there is only one possible candidate listed in the table: 11 O, posted on the arXiv and submitted for publication in December 2018. 25 If indeed only a few new isotopes are reported during the present year, another update of the discoveries of nuclides at the end of 2019 will not be warranted. The most current status will continue to be posted on the discovery project website.…”
Section: Discussionmentioning
confidence: 99%
“…The table contains five new isotopes: 24 N and 25 N were the subject of the Ph.D. thesis of Deshayes, 24 11 O was posted on the arXives by Webb et al, 25 and 79 Co and 84 Cu were reported in the most recent RIKEN Annual Report. 26 An additional three isotopes were presented at conferences and mentioned in the corresponding abstracts.…”
Section: Discoveries Not Yet Published In Refereed Journalsmentioning
confidence: 99%